A dual inverter-based supercapacitor direct integration scheme for wind energy conversion systems - Jayasinghe, S. D. Gamini. (2013)
Interfacing converters used in connecting energy storage systems like supercapacitors and battery banks to wind power systems introduce additional cost and power losses. This paper therefore presents a direct integration scheme for supercapacitors used in mitigating short-term power fluctuations in wind power systems. This scheme uses a dual inverter topology for both grid connection and interfacing a supercapacitor bank. The main inverter of the dual inverter system is powered by the rectified output of a wind turbine-coupled permanent-magnet synchronous generator. The auxiliary inverter is directly connected to the supercapacitor bank. With this approach, an interfacing converter is not required, and there are no associated costs and power losses incurred. The operation of the proposed system is discussed in detail. Simulation and experimental results are presented to verify the efficacy of the proposed system in suppressing short-term wind power fluctuations.